Penerapan Metode Analitycal Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) pada Sistem Pendukung Keputusan untuk Pemilihan Indekos - Rizky Pakpahan; Muhammad Siddik Hasibuan; Rizky Ananda Pakpahan; Raissa Amanda Putri (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2026)
The high rate of development of science has had a significant impact on business activities in the world of education, resulting in a significant increase in public awareness to decide to pursue knowledge outside the region, even abroad, this triggers the need for students who are studying outside the region to find suitable temporary accommodation. One way that is needed for students to overcome the problem of housing is by renting a place to live in the area, for example, a boarding house. Various types of boarding houses and forms that have been offered by boarding house businesspeople are supported by adequate facilities and affordable prices. The application of the Analytical Hierarchy Process (AHP) and the Simple Additive Weighting (SAW) Method produces a good assessment in terms of calculating the values ​​of the criteria and solving in choosing a boarding house, so that accurate results are obtained in choosing a boarding house. After the assessment process with the AHP and SAW methods, the best boarding house recommendation was A7 (Million boarding house) with a value of 0,876